Analysis Of Exchange Rate Differences And Foreign Currency Transactions In The Financial Statements Of PT. Smartfren Telecom Tbk - Nabila Maharani Rahayu; Nabila Putri Maharani; Nadya Eka Juliana; Novia Rizki (Fakultas Bisnis, 2025)
Companies all over the world now transact in a variety of foreign currencies due to globalization and the growth of international markets. One of the leading technology companies on the Indonesia Stock Exchange, PT. Smartfren Telecom Tbk., also faces complicated foreign currency transactions. The company frequently conducts cross-border transactions, which requires careful monitoring and reporting on foreign currency transactions and exchange rate differences. The purpose of this study is to find out the difference in exchange rates and foreign currency transactions in the consolidated financial statements and to evaluate how effective the policies and practices used by PT. Smartfren Telecom Tbk. in managing foreign currency risk. The analysis method in this study uses a quantitative descriptive approach, where data is collected through a literature review of various articles, journals, literature, and other references that are relevant to data sources derived from the Annual Report and Notes on the Financial Statements (CALK) of PT. Smartfren Telecom Tbk in 2023. The results of this study show that foreign currency transactions and exchange rate differences have been treated in accordance with PSAK 221. In preparing its consolidated financial statements, PT. Smartfren Telecom Tbk. complies with PSAK 221 on the use of foreign currency. In addition, the company has recognized the exchange rate difference in the income statement precisely, so that its financial statements accurately reflect financial performance in the context of exchange rate changes.